1995
DOI: 10.1192/bjp.166.1.80
|View full text |Cite|
|
Sign up to set email alerts
|

Placebo-Controlled Trial of Lithium Augmentation of Fluoxetine and Lofepramine

Abstract: Our results confirm that LA is a useful strategy in the treatment of antidepressant-resistant depression. Partial response was, however, frequently observed with continued antidepressant treatment alone, and the superiority of LA appears to depend on achieving adequate serum lithium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 13 publications
2
82
0
5
Order By: Relevance
“…The efficacy of lithium augmentation has been well documented in placebo-controlled acute (Joffe et al 1993;Katona et al 1995;Baumann et al 1996) and continuation treatment trials (Bauer et al 2000;Bschor et al 2002) using different classes of antidepressants. A recent meta-analysis confirmed the evidence that lithium augmentation is superior to placebo augmentation for the treatment of unipolar major depression, with a median response rate of 50% across double-blind studies (Bauer and Döpfmer 1999).…”
Section: On the Next Day) Twenty-four Patients Were Reassessed Aftmentioning
confidence: 99%
“…The efficacy of lithium augmentation has been well documented in placebo-controlled acute (Joffe et al 1993;Katona et al 1995;Baumann et al 1996) and continuation treatment trials (Bauer et al 2000;Bschor et al 2002) using different classes of antidepressants. A recent meta-analysis confirmed the evidence that lithium augmentation is superior to placebo augmentation for the treatment of unipolar major depression, with a median response rate of 50% across double-blind studies (Bauer and Döpfmer 1999).…”
Section: On the Next Day) Twenty-four Patients Were Reassessed Aftmentioning
confidence: 99%
“…However, few studies were conducted on SSRI nonresponders. Most of those studies were open label, and the results confirmed that augmentation with lithium was effective in TRD (Table 2) [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Level 1: Lithiummentioning
confidence: 97%
“…Entre os estudos, 14 utilizaram tricíclicos, seis utilizaram inibidores seletivos da recaptação da serotonina (ISRS), dois utilizaram inibidores da monoamina oxidase (IMAO) e dois utilizaram outras classes de antidepressivos. Dos 14 trabalhos envolvendo tricíclicos, nove utilizaram apenas esses fármacos (De Montigny et al, 1983;Cournoyer et al, 1984;Kantor et al, 1986;Dinan e Barry 1989;Browne et al, 1990;Stein e Bernardt 1993;Joffe et al, 1993;Hoencamp et al, 1994;Nierenberg et al, 2003) e cinco envolveram dois ou mais antidepressivos (Heninger et al, 1983;Zusky et al, 1988;Schopf et al, 1989;Katona et al, 1995;Rybakowski et al, 1999). Os IMAO foram utilizados em apenas dois ensaios, provavelmente devido ao fato de em geral serem empregados em etapas mais tardias da resistência ao tratamento e, também, devido aos riscos inerentes aos mesmos (Tabela 1).…”
Section: Lítiounclassified
“…Apesar da controvérsia, recomenda-se a utilização do lítio em níveis terapêuticos (Rouillon e Gorwood, 1998). Quanto ao tempo de latência, embora haja relato de melhora significativa em apenas 48h após adição de lítio (De Montigny et al, 1983), observou-se que a maioria dos pacientes apresentou melhora após a primeira (Heninger et al, 1983;Stein e Bernardt, 1993;Joffe et al, 1993;Baumann et al, 1996), a segunda ou a sexta semana de potencialização (Katona et al, 1995). Portanto, tendo em vista essas variações no tempo de resposta, sugeriu-se o emprego do lítio por, no mínimo, três (Rouillon e Gorwood, 1998) a seis semanas (Katona et al, 1995).…”
Section: Lítiounclassified
See 1 more Smart Citation